Artificial insemination of gilts with bovine viral diarrhea virus-contaminated semen - Storino, Gabriel Y. [UNESP]; Mechler-Dreibi, Marina L. [UNESP]; Xavier, Eduarda B. [UNESP]; Fioroto, Artur S. [UNESP]; Oliveira, Maria E. F. [UNESP]; Pituco, Edviges M.; De Oliveira, Luis G. [UNESP] (Canadian Vet Med Assoc, 2021)
Bovine viral diarrhea virus (BVDV) is a pestivirus that infects swine and other species and has genetic and antigenic similarity to classical swine fever virus. The objective of this study was to mimic the infection of swine by contaminated semen and evaluate the effects on their reproductive tracts and litters. Six gilts were artificially inseminated with semen containing BVDV-2 ncp (LVB 16557/15) and 2 were inseminated with BVDV-free semen. Blood samples from all gilts were collected for polymerase chain reaction and virus neutralization tests. No viremia or neutralizing antibodies were detected, and all the litters were born healthy.